Hawalah sebagai Alternatif Pembiayaan Multijasa di Lembaga Keuangan Syariah - Syakur, Ahmad (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2010)
Islamic banking and other Islamic financing institution need more inovationand to multiply the kind of transaction so that not to stay behind by conventional financing instituon. In the otherhand, hawalah that we know in the study of fiqh mu’amalah do not develop optimately in the Islamic economy institution. The application of hawalah in Islamic banking is little and not popular, whereas by little inovation, hawalah can be the alternative transaction. This article is an exertion to create the financing concept of multijasa Islamic Banking that more acceptable and more simple by using the hawalah contract with little inovation. That is the combination between hawalah bi al-ujrah contract and wakalah contract, as the alternative financing for increasing monetary instruments bases the sharia. So the strong and healty financing institution is realized without leaving the sharia